(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2026)
The issue of effectively implementing e-learning in higher education is debated in developing countries, including Nepal, Indonesia, Sri Lanka, Pakistan, Bhutan, and others. The primary objective of this study was to review forty published articles from 2015 to 2025, specifically those addressing the challenges of implementing inclusive e-learning in higher education between Nepal and Indonesia, and to find the similarities and differences in the challenges of implementing it. This study employed the literature review methodology to identify key information in each selected article. The results identified technological and infrastructural challenges as the primary challenges of implementing inclusive e-learning in higher education in Nepal and Indonesia. Most studies highlighted inadequate ICT infrastructure, unreliable internet, and unstable electricity as significant barriers to the adoption of e-learning. The results further highlighted that the high cost of digital devices and poor institutional support further limit accessibility. The next challenge was the digital literacy gap, as numerous studies have demonstrated that both students and educators struggle with digital skills, underscoring the need for faculty training and pedagogical support. The results conclude that the third challenge of implementing inclusive e-learning in higher education leads to socioeconomic disparities because different studies have shown that educational inequalities are reinforced, particularly for students from marginalized backgrounds who lack access to digital resources. The implications of this benefit higher education educators, policymakers, academicians, school administrators, principals, and young researchers in understanding the current barriers to digitization in higher education and formulating digital policies within their respective organizations.